2018
DOI: 10.5539/jas.v10n10p213
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Citrus Root System to Overcome a Strong Wax Layer

Abstract: The present work aimed to investigate the effects of mechanical impedance of wax layer (wax discs were installed 0.1 m deep) on root system deepening of citrus seedlings growing in columns with sand and nutrient solution. Two planting systems were evaluated: direct seeding (DS) and planting of seedlings (PS) (plants obtained from seed germination in tubes). Two experiments were carried out in a sequence: first to investigate the wax layer resistance levels (0.14 to 2.7 MPa) on root system penetration and two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Total root length and root length for the diameter classes tended to decrease in subsurface, and PNT was superior to PS along the profile (Figure 2). The results corroborate the fact that the presence of physical impediments to root growth close to soil surface (Table 1) increases root diameter, because it is an adaptive response to this abiotic stress (Gregory et al, 2009), as observed by Oliveira et al (2018) for citrus. L. D. Souza, Ribeiro, L. S. Souza, Ledo, and Cunha Sobrinho (2006) also observed, in 'Valencia' orange grafted on 'Volkamer' lemon (C. volkameriana Ten.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Total root length and root length for the diameter classes tended to decrease in subsurface, and PNT was superior to PS along the profile (Figure 2). The results corroborate the fact that the presence of physical impediments to root growth close to soil surface (Table 1) increases root diameter, because it is an adaptive response to this abiotic stress (Gregory et al, 2009), as observed by Oliveira et al (2018) for citrus. L. D. Souza, Ribeiro, L. S. Souza, Ledo, and Cunha Sobrinho (2006) also observed, in 'Valencia' orange grafted on 'Volkamer' lemon (C. volkameriana Ten.…”
Section: Resultssupporting
confidence: 85%
“…When the data were analyzed along with those of plant shoots, it was observed that the higher activity of the root system of plants grown from PNT, compared to PS, led to higher vegetative vigor in PNT, since it favored the increase in the canopy volume (CV) and vegetative vigor index (VVI) of young 'Pera' orange plants, in comparison to PS (Figures 1 and 2, Tables 3 and 4). In protected environment, Oliveira et al (2018) also verified that conventional planting (PNT) was associated with greater root and shoot vigor, indicating that, in soils with good physical structure and porosity or allowing root deepening beyond the cohesive layer, this planting system is completely adequate, despite the possible benefit of not cutting the pivoting root in direct sowing (PS). Davoglio Junior, Bordin, and Neves (2006) demonstrated the existence of correlation between the shoots and root system of 4-year-old citrus trees, due to the higher seedling vigor at planting and to the horizontal exploration of the soil by the roots.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The PSD practice for citrus supposes to result in a higher root deepening because the original architecture of the root system remains intact (Rezende, 2013;Rezende et al, 2015). However, there was no difference in root deepening system between planting types as also found in field conditions by Oliveira et al (2018) in a greenhouse study, in which the PPS of SCRL was correlated to higher root and shoot vigor, despite possible benefits of not cutting the pivoting root in the direct sowing.…”
Section: Resultsmentioning
confidence: 61%